2023
DOI: 10.1037/xan0000348
|View full text |Cite
|
Sign up to set email alerts
|

Flexible control of Pavlovian-instrumental transfer based on expected reward value.

Abstract: The Pavlovian-instrumental transfer (PIT) paradigm is widely used to assay the motivational influence of reward-predictive cues, reflected by their ability to invigorate instrumental behavior. Leading theories assume that a cue's motivational properties are tied to predicted reward value. We outline an alternative view that recognizes that reward-predictive cues may suppress rather than motivate instrumental behavior under certain conditions, an effect termed positive conditioned suppression. We posit that cue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 70 publications
4
5
0
Order By: Relevance
“…Another possible interpretation of our findings is that the response slowing under large stake magnitudes is an instance of positive conditioned suppression as previously reported in rodents (Azrin & Hake, 1969; Marshall, Halbout, Munson, Hutson, & Ostlund, 2023; Van Dyne, 1971). In positive conditioned suppression, cues signaling the immanent receipt of a reward suppress responding.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Another possible interpretation of our findings is that the response slowing under large stake magnitudes is an instance of positive conditioned suppression as previously reported in rodents (Azrin & Hake, 1969; Marshall, Halbout, Munson, Hutson, & Ostlund, 2023; Van Dyne, 1971). In positive conditioned suppression, cues signaling the immanent receipt of a reward suppress responding.…”
Section: Discussionsupporting
confidence: 85%
“…However, this suppression can extend backwards in time such that it even affects the instrumental response required to obtain the reward (i.e., a lever press). A recent study found small rewards to invigorate responding in line with classical PIT findings (Marshall et al, 2023). However, large rewards suppressed instrumental lever pressing and diminished PIT effects, suggestive of positive conditioned suppression interfering with PIT in a way similar of our findings.…”
Section: Response Slowing As Positive Conditioned Suppressionsupporting
confidence: 91%
See 3 more Smart Citations